The Effectiveness of Student Team Achiement Divisions (STAD) Cooperative Learning In Science Learning On Analysis Skills and Social Skills - Yunita Aryanti; Eko Widodo (Universitas Negeri Yogyakarta, 2020)
The purpose of this study is (1) to know the effectiveness of the application of STAD cooperative learning to the ability of analysis, to know the effectiveness (2) the application of the STAD type of cooperative learning to the social skills of students in science subjects, and (3) to know the effectiveness of the application of type cooperative learning STAD on students' analytical skills and social skills of students in natural science subjects. This type of research is a quasi-experimental design with a non-equivalent control group. The population in this study were all class VII SMP Negeri 4 Wonosari, amounting to 5 classes. Sampling was done by cluster random sampling technique. The sample of this study, namely class VII A as an experimental class and class VII B as a control class. Research instruments in the form of (1) multiple choice question sheets to determine students' analytical skills, (2) social skills questionnaire sheets, and (3) observation sheets of social skills used during learning. Hypothetical test is parametric through the MANOVA test, followed by the calculation of Cohen's effect size. The results showed that (1) the STAD type cooperative learning model was effective in increasing students' ability to analyze science in science subjects, (2) the STAD type cooperative learning model was effective in increasing the social skills of students in science subjects, and (3) the cooperative learning model STAD type is effective for improving students' analytical skills and social skills in natural science subjects.